Multinational corporations and sustainable development goals: Examining Etisalat Telecommunication intervention in Nigeria's basic education. Issue 1 (30th August 2019) - Bello, Ismail; Othman, Muhammad Fuad
Abstract : Purpose: There are over 263m out-of-school children in the world, and Nigeria is not an exception to the problem facing basic education. Education provides the necessary skills and knowledge needed by people in other to live a better life. The purpose of this paper is to explore the role of multinational corporations (MNC) towards basic education development in Nigeria using Etisalat Telecommunication as a case study. Design/methodology/approach: A qualitative method of data collection and analysis was used for the study. Interviews were conducted with 15 participants. NVivo software was utilized in transcription, coding and analysis of data from the interview conducted. Findings: Findings from the research revealed that Etisalat has made a significant contribution towards the development of the education sector in Nigeria, particularly basic education. This is evident in "adopt a school" initiative across the country. Etisalat intervention is in line with Sustainable Development Goal 4: quality education, which has led to improved infrastructure, school enrolment and most importantly improved quality of learning. Practical implications: This study will help educational institutions, government and international organization explore ways of utilizing private funds to develop basic education, not only in Nigeria but other climes around the world. Originality/value: This study adds to the literature on the role of non-state actors, especially MNC, towards developing the education sector in Nigeria. Previous studies have focussed on MNCs in other sectors; the use of Etisalat Telecommunication opens a new frontier in understanding the role of telecommunications MNCs in developing basic education in Nigeria.